Phase coexistence and grain size effects on the functional properties of BaTiO3 ceramics. Issue 5 (May 2022) - Lukacs, V.A.; Airimioaei, M.; Padurariu, L.; Curecheriu, L.P.; Ciomaga, C.E.; Bencan, A.; Drazic, G.; Avakian, M.; Jones, J.L.; Stoian, G.; Deluca, M.; Brunner, R.; et al.
Abstract: The functional properties of a series of BaTiO3 ceramics, having grain sizes ranging from 75 nm to 2.25 μm, with polymorph coexistence around room temperature are presented. Large temperature ranges of phase coexistence were detected through structural analyses, with no apparent size effect on the extension of co-existence domain, while the transition temperatures vary with grain size. Permittivity values are among the highest reported and the typical maximum around 1 μm grain size is confirmed by low field measurements and sub-switching Rayleigh analysis. An interesting feature not reported elsewhere is the persistence of permittivity maximum above Curie temperature and under high dc field at saturation, where domain walls contribution is minimal, raising questions about the largely accepted interpretation concerning the domain walls role on permittivity maximum. The planar defects in the starting powders give rise to extended strained defects in the ceramics, impacting their functional properties and multi-phase character.